7(y+2)+y=4(y+2)+7

Simple and best practice solution for 7(y+2)+y=4(y+2)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(y+2)+y=4(y+2)+7 equation:


Simplifying
7(y + 2) + y = 4(y + 2) + 7

Reorder the terms:
7(2 + y) + y = 4(y + 2) + 7
(2 * 7 + y * 7) + y = 4(y + 2) + 7
(14 + 7y) + y = 4(y + 2) + 7

Combine like terms: 7y + y = 8y
14 + 8y = 4(y + 2) + 7

Reorder the terms:
14 + 8y = 4(2 + y) + 7
14 + 8y = (2 * 4 + y * 4) + 7
14 + 8y = (8 + 4y) + 7

Reorder the terms:
14 + 8y = 8 + 7 + 4y

Combine like terms: 8 + 7 = 15
14 + 8y = 15 + 4y

Solving
14 + 8y = 15 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
14 + 8y + -4y = 15 + 4y + -4y

Combine like terms: 8y + -4y = 4y
14 + 4y = 15 + 4y + -4y

Combine like terms: 4y + -4y = 0
14 + 4y = 15 + 0
14 + 4y = 15

Add '-14' to each side of the equation.
14 + -14 + 4y = 15 + -14

Combine like terms: 14 + -14 = 0
0 + 4y = 15 + -14
4y = 15 + -14

Combine like terms: 15 + -14 = 1
4y = 1

Divide each side by '4'.
y = 0.25

Simplifying
y = 0.25

See similar equations:

| 8y=3y+18 | | d^2+5/2d+3/2=0 | | 6x+6-2x=1+3x-1 | | 6y=4x | | 28ab-7a-8b+2= | | -250.00+75.00w=500.00 | | 9-5x=3x-46 | | x^1/3=0 | | 5/6x=-10 | | (4x-2)=90 | | x^4-3-x^3+125=0 | | 5z=12-22 | | 4x^2-1-x(2x+1)=0 | | 1+(x-3)/3=(2x+1)/6-2 | | 0=3y^2-19y+22 | | 2x+8=-31+7x | | x^9+6-2x^5=1 | | 5v=3(v-1)+(3+2v) | | 15-1/10x=1/15x | | 4x^4=12x^3 | | -7=-46 | | 2x/4+x/8=5 | | 8(x+3)-(5x-9)=8 | | 3+-4=4(t+7) | | 10x+1+9+11x=180 | | 8x+24+-5x+-9=8 | | 8x+24+-5+-9=8 | | 3x-4=7x-1 | | w^5+24w^4=-144w^3 | | -x-1/7=x+1/4+2/7 | | 2z^5=32 | | 100-3x=10 |

Equations solver categories